2014
DOI: 10.3390/s140508895
|View full text |Cite
|
Sign up to set email alerts
|

A Vision-Based System for Intelligent Monitoring: Human Behaviour Analysis and Privacy by Context

Abstract: Due to progress and demographic change, society is facing a crucial challenge related to increased life expectancy and a higher number of people in situations of dependency. As a consequence, there exists a significant demand for support systems for personal autonomy. This article outlines the vision@home project, whose goal is to extend independent living at home for elderly and impaired people, providing care and safety services by means of vision-based monitoring. Different kinds of ambient-assisted living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 48 publications
0
66
0
1
Order By: Relevance
“…These, in turn, are employed for action recognition, where temporal alignment of sequences is performed for matching using dynamic time warping (DTW). Also multi-view recognition is taken into account [5]. Concretely, intelligent feature fusion of single-view feature representations is performed with a feature concatenation operator in addition to a weighted feature fusion scheme that is based on a priori knowledge about the usefulness of each camera.…”
Section: Human Action Recognition Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These, in turn, are employed for action recognition, where temporal alignment of sequences is performed for matching using dynamic time warping (DTW). Also multi-view recognition is taken into account [5]. Concretely, intelligent feature fusion of single-view feature representations is performed with a feature concatenation operator in addition to a weighted feature fusion scheme that is based on a priori knowledge about the usefulness of each camera.…”
Section: Human Action Recognition Methodsmentioning
confidence: 99%
“…Great advances have been made in order to improve the recognition rate, support multiple views and view-invariant recognition [2,3] as well as real-time performance [4,5]. However, it can be observed that HAR has been addressed by classifying short video sequences that contain single actions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, video data analysis allows one to identify specific actions, long term activities, and behavioural patterns [9], with some exploiting contextual information [11]. While video based platforms offer the opportunity to extract unique, continuous, and rich information from the home environment, they also present a number of disadvantages, such as privacy issues [9], user acceptance and system cost and scalability. Finally, the accepted challenges of computer vision, such as arbitrary body poses, changing illumination, occlusion, and low cost/low resolution are still unsolved problems [23] even if depth data is combined with colour [6].…”
Section: Introductionmentioning
confidence: 99%
“…Video based systems are efficient for implementing alert systems to detect dangerous events like falls, as in [20]. Furthermore, video data analysis allows one to identify specific actions, long term activities, and behavioural patterns [9], with some exploiting contextual information [11]. While video based platforms offer the opportunity to extract unique, continuous, and rich information from the home environment, they also present a number of disadvantages, such as privacy issues [9], user acceptance and system cost and scalability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation